Baihetan - Jiangsu engineering soil and water conservation online monitoring data system. Issue 1 (1st February 2023) - Lei, Lei; Song, Ji Ming; Wang, Jin; Hai Zheng, Shu; Yi Li, Feng; Wan, Hao
Abstract: Baihetan - Jiangsu ± 800kV UHVDC project can improve the power supply stability of the hydropower station, which has very important economic significance. The construction of power transmission projects will affect the water and soil conservation situation along the site. Currently, the commonly used monitoring methods are based on manual data collection with low accuracy and a large workload. Therefore, the government vigorously promotes the development of intelligent water conservancy and strives to improve the digitalization degree of water and soil monitoring systems. In this paper, the traditional chain pin method was improved, using the photosensitive chain pin and ultrasonic chain pin instead of the ordinary chain pin. Then calculated the soil erosion modulus by collecting the soil loss index of the measured point, and uploading it to the cloud for analysis by the radio transmission device, so that the monitor system obtained accurate soil loss data. Finally, the system is applied to the baihetan-Jiangsu soil and water conservation monitoring project, and the monitoring data of soil and water conservation of the two stations are obtained. Combined with the local meteorological conditions, we can analyze the causes of soil and water loss, and give the corresponding prevention measures.